Consumers' emotional responses evoked by fermented rice noodles containing crickets and/or mango peel: impact of product information and prior insect consumption. (16th July 2022) - Maw, Win Win; Sae‐Eaw, Amporn; Wongthahan, Peerapong; Prinyawiwatkul, Witoon
Summary: Expected sensory liking and emotional profiles of three fermented rice noodles containing cricket (P‐cp), mango peel (P‐mp) and a combination of cricket and mango peel (P‐cp*mp) were virtually evaluated using an online survey ( n = 727 consumers). Data were grouped by consumers as follows: consumers, who had consumed cricket, participating in the online survey before (C‐eb) or after (C‐ea) receiving product information; and consumers, who had never consumed cricket, participating in the online survey before (C‐nb) or after (C‐na) receiving product information. Expected overall sensory liking and emotional profiles were analysed using ANOVA and Correspondence Analysis, respectively. C‐ea rated all products with the highest expected sensory liking scores. P‐cp and P‐cp*mp evoked more negative emotions than did P‐mp. Consumers who did not receive information and/or those who never consumed crickets mainly expressed negative emotions. More specifically, C‐ea mostly exhibited positive emotions, whereas C‐na elicited more negative emotions for all products. This study concluded that consumers' expected sensory liking and emotional profiles of fermented rice noodles containing cricket (P‐cp) were influenced by additional product information and prior cricket consumption experience. This finding would be useful for introduction of products containing cricket. Abstract : Expected sensory liking and emotional profiles of cricket and/or mango peel based fermented rice noodles.